Immunotherapy and the Spectrum of Kidney Disease: Should We Individualize the Treatment? - Bermejo, Sheila; Bolufer, Mónica; Riveiro-Barciela, Mar; Soler, Maria José (Frontiers in Medicine, 2022)
The new targeted cancer therapies including immune checkpoint inhibitors (ICI) have demonstrated to improve the survival of oncological patients, even in metastatic cancers. In the last five years, several studies have revealed that ICI can produce several immune-mediated toxicities involving different organs, such as skin, gastrointestinal tract, liver, and, of course, the kidney. The most frequent lesion of immunotoxicity in the kidney is acute interstitial nephritis (AIN), although other nephropathies have also been described as a consequence to the use of ICI, such as glomerulonephritis and acute thrombotic microangiopathy, among others. In addition, kidney rejection has also been reported in kidney transplant patients treated with ICI. Normally randomized clinical trials with ICI exclude patients with end-stage kidney disease namely dialysis and kidney transplant patients. Several important questions need to be addressed in relation with immunotherapy and kidney disease patients: a) when to start corticosteroid therapy in a patient with suspected acute kidney injury (AKI) related to ICI, b) the moment of nephrologist referral and kidney biopsy indication, c) management of ICI in dialysis patients; d)ICI in kidney transplantation, immunosuppressive personalized treatment and risk of allograft rejection in kidney transplant patients. The objective of this review is to summarize the recent published literature in a wide spectrum of kidney disease patients with cancer and ICI. This review will address three main important groups of individuals with kidney disease and cancer immunotherapy, acute kidney injury associated with ICI, dialysis patients and kidney transplant recipients. We believe the information provided in this review will enlighten the personalized ICI treatment in individuals with a broader spectrum of kidney disease.